THE CATALYTIC ACTIVITY OF THE DEVELOPING HEN'S EGG - Winternitz, M. C. (The Rockefeller University Press, 1910)
A. The catalytic activity of the tissues of newly born and adult rabbits. 1. There is practically no difference between the catalytic power of the blood, brain or muscle of newly born and adult rabbits. 2. The kidneys and lungs are less active in the newly born, but increase rapidly during the first days of life. 3. The liver is more active in the newly born than in the adult rabbit. B. The catalytic activity of the developing hen's egg. 1. The entire fresh egg has a slight but definite catalytic power which remains practically constant even though the egg be kept for several months at room temperature. 2. The separate parts of the egg, germinal center, yolk and white have practically no activity when tested individually. 3. The entire unfertilized egg shows no catalytic activity even after incubation at 38° C. for twenty-one days. 4. The germinal portion of the incubated fertilized egg rapidly acquires the power of decomposing hydrogen peroxide, while the yolk and white together or separately show no such increase, nor is there any activity to be found in the amniotic fluid. 5. It seems, therefore, that the catalytic power of the developing egg is formed from the contents of the egg which themselves show little action, by the developing germinal portion, independent of all external influences except heat (38° C.) and air.